Optimasi Website Sampurna Berkah dengan Framework Scrum Menggunakan Metode Agile untuk Meningkatkan Penjualan - Pratiwi, Aniec Anafisah; Tanfitra, Adhim; Waluyo, Bibit; Abid, Umar Abdul; Tarwoto (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Waste management has become a complex national issue in Indonesia, driven by population growth, economic expansion, and shifting consumption patterns. The Sampurna Berkah website, owned by Sidapurna Village, Dukuhturi District, Tegal Regency, was created to support an environmentally conscious community focused on recycling non-biodegradable waste. To effectively develop the information system for this website, an agile approach is essential. The Scrum framework is employed to enhance transparency, communication, documentation, and adaptability to change. This study aims to optimize the Sampurna Berkah website, which has existing issues such as a confusing user interface, unsuitable color combinations, and lack of responsiveness. Using the Agile Scrum method, stages like Product Backlog, Sprint Planning, Sprint Backlog, Daily Scrum, and Sprint Review were implemented. The optimization results show significant improvements, including a more user-friendly interface, better website responsiveness, and more visually pleasing color combinations, achieving the main development objectives.